2023
DOI: 10.1038/s41413-023-00247-y
|View full text |Cite
|
Sign up to set email alerts
|

Fighting age-related orthopedic diseases: focusing on ferroptosis

Abstract: Ferroptosis, a unique type of cell death, is characterized by iron-dependent accumulation and lipid peroxidation. It is closely related to multiple biological processes, including iron metabolism, polyunsaturated fatty acid metabolism, and the biosynthesis of compounds with antioxidant activities, including glutathione. In the past 10 years, increasing evidence has indicated a potentially strong relationship between ferroptosis and the onset and progression of age-related orthopedic diseases, such as osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 292 publications
(394 reference statements)
0
18
0
Order By: Relevance
“…In the classical model, Fe 2+ is involved in a variety of biochemical processes within the BCEC, including efflux. There are two storage forms of iron in the cell: stable ferritin and active unbound iron, namely the unstable iron pool (LIP) (Ru et al 2023 ). Excess reactive Fe 2+ as LIP can cause ROS accumulation through Fenton reaction (Yan et al 2021b ).…”
Section: Iron Metabolismmentioning
confidence: 99%
“…In the classical model, Fe 2+ is involved in a variety of biochemical processes within the BCEC, including efflux. There are two storage forms of iron in the cell: stable ferritin and active unbound iron, namely the unstable iron pool (LIP) (Ru et al 2023 ). Excess reactive Fe 2+ as LIP can cause ROS accumulation through Fenton reaction (Yan et al 2021b ).…”
Section: Iron Metabolismmentioning
confidence: 99%
“…PERK-eIF2α-ATF4 signal pathway was capable of ameliorating ferroptosis by up-regulating HSPA5 and System Xc - [ 35 , 36 ]. On the other hand, erastin-induced ER stress activates the PERK-eIF2α-ATF4-CHOP pathway, leading to an increase in PUMA expression, which participates in the regulation of ferroptosis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iron overload is common in the tissues of older adults, and ferroptosis plays an important role in the development of chronic diseases. Recent studies have shown that ferroptosis, characterised by the lethal accumulation of reactive iron and lipid peroxide, contributes to degenerative orthopaedic diseases [ 14 ], but ER exerts an anti-ferroptosis effect [ 15 ].…”
Section: Introductionmentioning
confidence: 99%